A new antifungal compound from Streptomyces diastatochromogenes - Ming-Yun Wang; Ke-Qi Ye; Dan-Ting Li; Chun-Li Guo; Jia-Cheng Ge; Xiao-Ping Yu; Xu-Ping Shentu (BMC Biotechnology)
Abstract Novel antifungal compounds effective against phytopathogenic fungiwere identified by evaluating an n-butanol extract obtained from the fermentation broth of Streptomyces diastatochromogenes strain No.1628. The extract exhibited had strong antifungal activity against Botrytis cinerea, Fusarium oxysporum, and Rhizoctonia solani, markedly reducing the spore germination rates of F. oxysporum and B. cinerea to 25.65% and 28.23%, respectively, at a concentration of 35 mg/L. In vivo efficacy assays further demonstated that the extract achieved disease control efficiencies of 53.42% and 55.68% against Rhizoctonia rot following irrigation at 10 mg/L for 14 and 21 days, respectively. Subsequent chemical investigation led to the isolation of five antifungal compounds from the n-butanol extract: the novel tetraene macrolide, which was structurally elucidated through spectroscopic analysis as (7E,12Z,13E,15E,17E,19E)-21- ((4-amino-3,5-dihydroxy-6-methyltetrahydro-2 H-pyran-2-yl)oxy -)-12-ethylidene-1,5,6,25-tetrahydroxy-11-methyl-9-oxo-10,27-dioxabi-cyclo[21.3.1] -heptacosa-7,13,15,17,19-pentaene-24-carboxylic acid (compound 1), and four other already known antifungal agents, namely tetrin B (2), tetramycin A (3), toyocamycin (4) and anisomycin (5). Compound 1 exhibited potent inhibitory activity against the hyphal growth of R. solani, F. oxysporum, and B. cinerea, with IC50 values of 0.20, 1.28, and 1.53 µg/mL, respectively. These fundings underscore S. diastatochromogenes as a promising microbial source for the discovery of natural antifungal agents.